Understanding the experiences of parents in developing interest and talent of children - Fadlillah, M.; Pangastuti, Ratna (Intelektual Pustaka Media Utama, 2025)
Every child has a talent that is ready to be developed. However, not all parents know how to identify and develop it. Purpose of the study is to explore and analyze the experiences of parents in developing interest and talent of children. In order to obtain factual data on parenting, a qualitative method was used. Data collection was carried out by in-depth interviews and open to seven parents of talented children. The data obtained were analyzed in five stages, namely transcribing the results of interviews, taking inventory of important statements, classifying meanings, describing and constructing the essence of the subject's experience, and making research reports. There were three main findings of this research, namely: i) parents in nurturing for talented children have the characteristics of an authoritative style, where demands and responses were carried out in a balanced manner, ii) the development of children's interest and talent was carried out by parents by guiding and training independently, taking lessons, and various competitions, and iii) limited time and energy were the main obstacles for parents in nurturing and developing children's interest and talent.